Copper-catalyzed radical trifluoroethylthiolation of arylboronic acids with PhSO2SCH2CF3. (2nd March 2022) - Dong, Lefeng; Liang, Junqing; Chen, Ruijia; Xu, Xiaoyong; Shao, Xusheng; Li, Zhong
Graphical abstract: Abstract: Trifluoroethylthio group (SCH2 CF3 ) is a key functionality in several pharmaceutical and agrochemical compounds, the methods for the installation of the 2, 2, 2-trifluoroethylthio group are sought after. Herein, we report a copper-catalyzed trifluoroethylthiolation reaction of S-(2, 2, 2-trifluoroethyl) benzenesulfonothioates and phenylboronic acids at room temperature. The reaction achieved the insertion of trifluoroethylthio moiety to efficiently obtain various substituted aryl 2, 2, 2-trifluoroethyl thioethers in good yields. Mechanistic investigation indicates the trifluoroethylthiolation radical is involved in the catalytic circle. Moreover, trifluoroethylthiolated clofibrate was synthesized in a particular fashion.